THE IMPACT OF PEAK MANAGEMENT SUPPORT, MOTIVATION AND INFORMATION TECHNOLOGY ON THE PERFORMANCE OF OS EMPLOYEES (OUTSOURCING) PT. PLN (PERSERO) ULP (CUSTOMER SERVICE UNIT) MEDAN SELATAN: DAMPAK DUKUNGAN MANAJEMEN PUNCAK, MOTIVASI DAN TEKNOLOGI INFORMASI TERHADAP KINERJA KARYAWAN OS (OUTSOURCING) PT. PLN (PERSERO) ULP (UNIT PELAYANAN PELANGGAN) MEDAN SELATAN - Arman Ndruru, Heri; Ganda Pandapotan Limbong, Marslam (UPMI Proceeding Series, 2023)
This research was conducted at PT. PLN ULP Medan Selatan which operates in the field of providing electricity for community needs. The aim of the research is to determine the effect of top management support, work motivation and information technology on employee performance. The population is 95 outsourced employees who work in the company. Sampling was taken using saturated samples so that the total sample was 95 respondents. The data source uses primary data and data collection is by survey, namely giving questionnaires to respondents. Data analysis techniques use data quality tests, classical assumption tests and hypothesis tests. Based on the results of research conducted, it shows that partially top management support and information technology have a positive and significant effect on the performance of outsourced employees, while work motivation has a positive but not significant effect on the performance of outsourced employees at PT. PLN ULP Medan Selatan. Simultaneously, top management support, work motivation and information technology simultaneously have a positive and significant effect on the performance of outsourced employees at PT. PLN ULP Medan The correlation between top management support, work motivation and information technology is very strong on the performance of outsourced employees at PT. PLN ULP Medan Selatan. The percentage of employee performance that can be explained by top management support, motivation and information technology is 72.4% and the remaining 27.6% can be explained by other variables that were not studied.